Penerapan Media Interaktif Power Point untuk Meningkatkan Aktivitas dan Hasil Belajar Siswa Kelas VI Tema 8 SDN Prantaan Kabupaten Blora - Wahyuningsih, Sustiana (UNDIKMA, 2022)
The purpose of this study was to increase student activity and learning outcomes by using interactive media Power Point for students of Class VI Theme 8 at SDN Prantaan. The research method used is Classroom Action Research (CAR) consisting of 3 cycles with 4 stages, namely planning, action, observation, and reflection. The subjects of this study were students of class VI with a total of 30 students. Data collection techniques used are observation, interviews, tests, and documentation. While the data analysis technique used descriptive analysis. The results of this study indicate that the average percentage of student activity classically has increased. In the pre-cycle before treatment it was 65%, in the first cycle it was 69%, in the second cycle it was 74% while in the third cycle it was 87%. While the percentage of mastery learning outcomes in the pre-cycle is 33%, in the first cycle it is 33%, in the second cycle it is 73%, while in the third cycle it is 90%. Based on the results of the research that has been done, it can be concluded that learning in Theme 8 using interactive power point media can improve student activities and learning outcomes.